2019
DOI: 10.35942/ijcab.v3iv.66
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Financial Control Mechanisms on Performance of Income Generating Units in Selected Public Universities in Kenya

Abstract: In an attempt to bridge the gap between the budgetary allocations and actual expenditures most universities have started income generating units with the aim of boosting their operational expenses. Whereas there is the potential of the use of Income Generating Units (IGUs) to generate additional funds, most universities still experience challenges in full implementation and realization of the revenue goal. This study therefore sought to determine the financial control mechanisms affecting performance of income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Leadership quality can be a moderator of the ICS (Alam et al, 2019;Dangi et al, 2020) and FV (Imam and Reza, 2016;Miranda et al, 2016). Previous research has found a relationship between ICSs and MIG (Adora, 2019;Towett et al, 2019;Yemer, 2017) moderated by LQ. A good ICS in MIG encourages universities to be more optimal in overcoming financial management problems.…”
Section: Leadership Qualitiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Leadership quality can be a moderator of the ICS (Alam et al, 2019;Dangi et al, 2020) and FV (Imam and Reza, 2016;Miranda et al, 2016). Previous research has found a relationship between ICSs and MIG (Adora, 2019;Towett et al, 2019;Yemer, 2017) moderated by LQ. A good ICS in MIG encourages universities to be more optimal in overcoming financial management problems.…”
Section: Leadership Qualitiesmentioning
confidence: 93%
“…Internal control is a continuous operation and an integrated system at all levels in an organization. Indicators of internal control include the control environment, risk assessment, control activities, information, communication and controlling (Towett et al ., 2019). The items developed are in the Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations